E-book: The emergence, purchasing methods and library return on investment / Che Zainab Hj Abdullah - Abdullah, Che Zainab (Faculty of Information Management, 2015)
This paper presents a perception study on e-book selection practices and its relationships with library's return on investment Return on Investment (ROI) is one method for measuring the value of a library's collections and services. The paper focuses on common practices of e-book selection regarding support distance education, sustainability and the introduction of patron driven acquisition (PDA) in developing e-book collection.